Analisis Risiko Saham Perusahaan Agriculture (Crops, Plantation, and Fishing) di Bursa Efek Indonesia - Astri Indah Utari; Khaira Amalia Fachrudin (Universitas Sumatera Utara, 2013)
Abstract The aims of this research is to determine and analyze the difference of systematic risk and unsystematic risk in crops subsector, plantation subsector, and fishing subsector in the Indonesia Stock Exchange. This research is descriptive and comparative research. Descriptive research is research to know the value of variable independent either one variable or more. Comparative research is a which are comparing. The population and samples in this research is the whole company on the crops subsector, plantation subsector, and fishing subsector in the Indonesia Stock Exchange from January 2012 – December 2012 is 15 companies. The analysis method used is One Way ANOVA. The research use secondary data . The result of this research indicates that there was no difference systematic risk and unsystematic risk between crops subsector, plantation subsector, and fishing subsector with alpha 0,05. The implication of this research are investors can invest on third subsector with same risk because there was no difference systematic risk and unsystematic risk between crops subsector, plantation subsector, and fishing subsector. Keywords : Systematic risk, Unsystematic risk, Crops subsector, Plantation subsector, and Fishing subsector.